2012
DOI: 10.1155/2012/817107
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Zinc Concentration in Grain of Durum Wheat in Relation to Phosphorus Fertilization, Crop Sequence and Tillage Management

Abstract: Field experiments were conducted at two locations in Manitoba, Canada, to determine the effect of crop rotation, phosphorus (P) fertilization and tillage on grain yield and grain concentrations of Cd and Zn in durum wheat (Triticum durum L.). Compared to conventional tillage (CT), reduced tillage (RT) management decreased grain Cd and increased grain yield and grain Zn in half of the site-years. The type of preceding crops of spring wheat-flax or canola-flax had little influence. Rate and timing of P applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…In contaminated soils, P-metal complex formation depends upon several factors such as type of P amendment, plant species, and excretion of organic acids by plant roots . However, phosphorus sources should be used with great attention, as there might be a risk of soil contamination with Cd due to Cd present in P fertilizers (Gao and Grant 2012). Thus, the use of gypsum amendment might be a suitable choice for metal stabilization in soil as compared to P amendments.…”
Section: Discussionmentioning
confidence: 99%
“…In contaminated soils, P-metal complex formation depends upon several factors such as type of P amendment, plant species, and excretion of organic acids by plant roots . However, phosphorus sources should be used with great attention, as there might be a risk of soil contamination with Cd due to Cd present in P fertilizers (Gao and Grant 2012). Thus, the use of gypsum amendment might be a suitable choice for metal stabilization in soil as compared to P amendments.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [80] reported that Zn might prevent Cd translocation from roots to shoots. Zinc and Cd are chemically similar and may compete for transport mechanisms during uptake and translocation in the crop [14]. Zhou et al [81] noted that Zn has antagonistic and synergistic effects on Cd uptake by plants.…”
Section: Using Zincmentioning
confidence: 99%
“…For example, a three-year rotational study on silt loam soil in southwestern Saskatchewan showed that durum wheat increased grain yields by 5% and grain protein concentration by 6% when following canola and mustard than following spring wheat, while the durum wheat increased grain yield by 7% and protein concentration by 11% when following pulse crops, relative to after spring wheat [9]. In Orthic Black Chernozemic soils in southern Manitoba, which is outside the durum wheat area, wheat-flax-durum and canola-flax-durum rotations repeated for three cycles showed that canola-flax as preceding crops led to greater subsequent durum wheat yield than wheat-flax as the previous crops in only one out of six site-years [90]. Many factors are involved in the inconsistent rotational effects, such as soil type [61] and agronomic practices [91].…”
Section: Soil Microbiomementioning
confidence: 91%